Experimental study on chip shape in ultrasonic vibration–assisted turning of 304 austenitic stainless steel - Yingshuai Xu; Zhihui Wan; Ping Zou; Qinjian Zhang (Advances in Mechanical Engineering, 2019)
There are many problems and physical phenomena in turning process, like machined surface quality, cutting force, tool wear, and so on. These factors and the chip shape of workpiece materials, which is an important aspect to study the mechanism of ultrasonic vibration–assisted turning, go hand in hand. This article first introduces the types and changes of chip, meanwhile the chip formation mechanism of ultrasonic vibration–assisted turning is studied and analyzed, and the turning experiments of 304 austenitic stainless steel with and without ultrasonic vibration are carried out. The difference of chip morphology between ultrasonic vibration–assisted turning and conventional turning is contrasted and analyzed from the macroscopic and microscopic point of view. The influence of process parameters on chip shape and the impact of chip shape on machining effect are also analyzed. Results indicate that when process parameters (vibration frequency, ultrasonic amplitude, and cutting parameters) are suitably selected, ultrasonic vibration–assisted turning can gain access to better chip shape and chip breaking effect than conventional turning. By contrast with conventional turning, phenomenon of serrated burr on the chip edge and the surface defects of chip in ultrasonic vibration–assisted turning have improved significantly. Moreover, it is found that superior chip morphology in ultrasonic vibration–assisted turning can be acquired under the circumstance of comparatively small cutting parameters (cutting speed, depth of cut, and feed rate); at the same time, preferable chips can also obtain ranking machining effect.